Kriminaliteta kot vse pomembnejši dejavnik kakovosti bivanja v ljubljanski urbani regiji - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
The increasingly extensive hinterland of Ljubljana is due to intensive suburbanization becoming an extremely transitional area with a typical intertwining of urban and rural sociogeographic elements. Among the effects of suburbanization we can certainly deal with the appearance and increase of criminal acts. The data for the year 2002 show that in the Ljubljana urban region there were registered more than 40 % of all criminal acts in Slovenia. By far most of them, almost 30 %, were registered in the Ljubljana municipality. The endangerment is more notably increasing in the other communities of the Ljubljana urban region, above all in those which were captured by the last wave of suburbanization.
Keywords: urbana geografija; mesta; urbanizacija; suburbanizacija; kriminaliteta; kazniva dejanja; bivalno okolje; kvaliteta; Slovenia; Slovenija